'This Helps You See Life Differently': Evaluating Youth Development and Capability Expansion in Remote Communities of Honduras. (April 2022) - Wyngaarden, Sara; Humphries, Sally; Skinner, Kelly; Tosta, Esmeralda Lobo; Portillo, Veronica Zelaya; Orellana, Paola; Dodd, Warren
Youth in rural Honduras experience barriers to accessing education, vocational training, and social supports for their formative development. This study evaluated over 18 years of youth-specific development interventions implemented by a Honduran organization in two rural municipalities. The study draws on 94 semi-structured interviews and demographic data from 1596 program participants. Three impact pathways were identified through which respondents experienced positive outcomes from program involvement: transformative participation; meaningful collaboration; and low-risk experimentation. The findings parallel known development theories and empowerment frameworks, including the Human Development and Capabilities Approach and Positive Youth Development, thus supporting the effectiveness of these approaches in facilitating youth development and capability expansion in remote Honduran communities.